PELANGGARAN SYARAT DOMISILI DALAM PENERAPAN GUGATAN SEDERHANA DI PENGADILAN NEGERI BANDA ACEH - Muhammad Razan Hilmi; Syamsul Bahri (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2025)
Small claim court is a procedure in civil litigation in which the trial can be conducted more quickly and simply compared to an ordinary lawsuit. To file a small claim court, certain criteria must be met as stipulated by regulation; however, in practice, violations often occur regarding the requirements that should be fulfilled. Violation of domicile requirements in the application of small claims court has the potential to undermine the purpose of simplified justice, and this article aims to explain the forms of such violations, the reasons behind their occurrence, and the judges’ responses at the Banda Aceh District Court. This article is empirical juridical with techniques to examine applicable legal provisions and what occurs in society. Data collection through library and field research, field research was conducted by interviewing respondents related to this article, library research was conducted by reading textbooks and regulations. The data obtained were analyzed descriptively to identify patterns and problems that exist in the application of the Small Claims system in the Banda Aceh District Court. The results of the study indicate that there are violations of the requirements in the application of the small claims system, namely related to the parties' understanding of the domicile requirements in accordance with the regulations. Practice in the field shows that there are discrepancies in the implementation of applicable regulations, the use of legal loopholes to avoid the article is a violation in the application of small claims. There is a need to increase the understanding of the parties through law enforcement or seminar forums regarding small claims procedures, especially related to domicile requirements. This can be done by the Supreme Court by clarifying the provisions in the regulations to reduce ambiguous interpretations